2020
DOI: 10.1080/19942060.2020.1711812
|View full text |Cite
|
Sign up to set email alerts
|

Use of computational fluid dynamics to implement an aerodynamic inverse design method based on exact Riemann solution and moving wall boundary

Abstract: An aerodynamic inverse design method, which is used in compressors, is introduced in this paper. This inverse design method is based on the exact solution of the local Riemann problem on moving blade surfaces. Furthermore, an improved relaxation factor is added to control the induced velocity for reasonable deformation sizes in different cases. The viscous flow analysis and the inverse design are integrated in the computational fluid dynamics software ANSYS Fluent using the dynamic mesh user-defined function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The reliability, stability, and convergence of the proposed ANN-BR algorithm were further certified by a mean squares errors based fitness metric, histogram illustrations, and regression analysis for each variant of the BCSNF model. In the future, new variants of artificial intelligence based integrated intelligent networks (Ahmadi, Sadeghzadeh, et al, 2019;Alotaibi et al, 2020;Duan et al, 2020;Park et al, 2020;Sabir et al, 2020) will be developed by the interested researcher for solving stiff/nonlinear/singular systems representing the fluid mechanics models (Ahmad et al, 2021;Ahmadi, Mohseni-Gharyehsafa, et al, 2019;Siddiqa et al, 2018;, circuit theory dynamics (Mehmood, Zameer, Aslam, et al, 2020, Mehmood, Zameer, Ling, et al, 2020, mathematical biological systems (Umar et al, 2020;Wang et al, 2020), information security models (Liu et al, 2020)), and astro/plasma/nuclear/atomic physics models (Bukhari et al, 2020;Ilyas et al, 2021;Jadoon et al, 2021;Zameer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability, stability, and convergence of the proposed ANN-BR algorithm were further certified by a mean squares errors based fitness metric, histogram illustrations, and regression analysis for each variant of the BCSNF model. In the future, new variants of artificial intelligence based integrated intelligent networks (Ahmadi, Sadeghzadeh, et al, 2019;Alotaibi et al, 2020;Duan et al, 2020;Park et al, 2020;Sabir et al, 2020) will be developed by the interested researcher for solving stiff/nonlinear/singular systems representing the fluid mechanics models (Ahmad et al, 2021;Ahmadi, Mohseni-Gharyehsafa, et al, 2019;Siddiqa et al, 2018;, circuit theory dynamics (Mehmood, Zameer, Aslam, et al, 2020, Mehmood, Zameer, Ling, et al, 2020, mathematical biological systems (Umar et al, 2020;Wang et al, 2020), information security models (Liu et al, 2020)), and astro/plasma/nuclear/atomic physics models (Bukhari et al, 2020;Ilyas et al, 2021;Jadoon et al, 2021;Zameer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies use the pressure difference method with the same concept of moving walls as well. [27][28][29] An overview of the blade design methods is illustrated in Figure 1. Choosing the inverse design method depends on the inputs to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…During the past couple of decades, the throughflow calculation has become one of the most important components for the multistage axial compressor design, and it still remains crucial roles in the aerodynamic design and optimization of axial compressors, 2 even though the advancement of computational power has made possible the fully three-dimensional calculation in the compressor design phase. 3,4 Traditional throughflow methods solve radial equilibrium equations on the meridional plane, such as the streamline curvature method developed by Smith 5 and the matrix throughflow method developed by Marsh. 6 In principle, they are different numerical approaches for the throughflow calculation as the streamline curvature method directly solves radial equilibrium equations, while the matrix throughflow method uses a stream function; however, as Davis 7 concluded that there is little to choose between them.…”
Section: Introductionmentioning
confidence: 99%